Fabrication of AO/LDH fluorescence composite and its detection of Hg2+ in water. Issue 1 (December 2017) - Liu, Meng; Lv, Guocheng; Mei, Lefu; Wei, Yanke; Liu, Jieyuan; Li, Zhaohui; Liao, Libing
Abstract Divalent mercury ion (Hg2+ ) is one of the most common pollutants in water with high toxicity and significant bioaccumulation, for which sensitive and selective detection methods are highly necessary to carry out its detection and quantification. Fluorescence detection by organic dyes is a simple and rapid method in pollutant analyses and is limited because of quenching caused by aggregation dye molecules. Hydrotalcite (LDH) is one of the most excellent carrier materials. In this study, an organic dye acridine orange (AO) was successfully loaded on the LDH layers, which significantly inhibited fluorescence quenching of AO. The composite AO/LDH reaches the highest fluorescence intensity when the AO initial concentration is 5 mg/L. With its enhanced fluorescent property, the composite powder was fabricated to fluorescence test papers. The maximal fluorescence intensity was achieved with a pulp to AO/LDH ratio of 1:5 which can be used to detect Hg2+ in water by naked eyes. Hg2+ in aqueous solution can be detected by instruments in the range of 0.5 to 150 mM. The novelty of this study lies on both the development of a new type of mineral-dye composite material, as well as its practical applications for fast detection.